Yancothulwa ingqambu - Komanisi, Nomnikelo (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
I have written a collection of isiXhosa poems for my thesis. I was influenced by the conditions in life women often find themselves, as well as the cultural stereotypes that perpetuate these conditions. Writers who have had an impact on my writing are W. B. Rubusana, S. E. K. Mqhayi and J. J. R. Jolobe because of their language, rhythm and the richness of their writing more generally. It is as if they are voices of a past generation who reach out on us, today. More recent American poets such as Amiri Baraka, on the other hand, have shown me how poems can meet you, can come as bullets that pierce your heart, soul and brain. Combining these old and new poetic styles, I intend for my poems to be of value and benefit to women who seek mental, spiritual and physical healing.
Keywords: Xhosa poetry -- 21st century; Women in literature; Stereotypes (Social psychology) in literature; Xhosa poetry -- 21st century fiction -- History and criticism